Internship Students’ Workplace Communication Skills: Workplace Practices and University Preparation - Bhattacharyya , Ena; Md Nordin, Shahrina; Salleh, Rohani (CGPublisher, 2009)
A graduate’s ability to communicate effectively can greatly affect their career development in the future workplace. Communication lecturers need to be equipped with the knowledge of the communicative needs of their technical students’ future working environment. With such awareness and knowledge, lecturers are able to make learning more relevant and meaningful and ease the transition of undergraduates from an academic setting to the workplace environment. Questionnaires were given to a set of final year technical students who had just returned from their 8-month industrial internship training at various organizations. The study identified essential oral internal and external workplace communication activities of the organization. Feedback was also obtained from the students’ with regard to the university practices and preparation required for workplace communication. The findings of this research will also provide an insight into the adequacy of university preparation for effective communication in an environment far different from the university setting. Thus, guiding these students in accordance with workplace requirements will not only bring about relevant and meaningful learning, but also result in effective participation in the said discourse community. The paper will also discuss the pedagogical implications of its findings.